Constraints and Solutions to Problems in Online Learning at SD Kristen Satya Wacana, Salatiga - Fidelis Alvin Basundara Prima; Eunice Widyanti Setyaningtyas (Salasika, 2022)
The Covid-19 pandemic has had a significant impact on the world of education. Therefore, the government, through the relevant ministries, makes crucial policies by imposing distance or online learning. In an effort to support this learning, the government has also implemented an internet quota program for students by deactivating various social media so that students focus on learning. However, it cannot be denied that there are obstacles in learning. The results of the questionnaire show that network constraints play a major role in learning. With intermittent sound, the network which often crashes is enough to disrupt the online learning process. The solution offered by students' parents is to change the provider or wait until the network is normal. The dominant solution in the results of this study is to carry out learning variations, namely face-to-face and online as well as recording material and adding learning applications so that if there is a disruption to the learning network, the learning continues because the material is already stored on the students' or parents' mobile phones. All obstacles can be overcome thanks to good cooperation between schools, especially support teachers, parents and students.